Birth Order in the Very Long-Run: Estimating Firstborn Premiums between 1850 and 1940 - Angela Cools; Jared Grooms; Krzysztof Karbownik; Siobhan O'Keefe; Joseph Price; Anthony Wray (Institute of Labor Economics (IZA), 2024)
The nineteenth-century American family experienced tremendous demographic, economic, and institutional changes. By using birth order effects as a proxy for family environment, and linked census data on men born between 1835 and 1910, we study how the family's role in human capital production evolved over this period. We find firstborn premiums for occupational outcomes, marriage, and fertility that are similar across census waves. Our results indicate that the returns to investments in the family environment were stable over a long period.
Keywords: J13; J62; N30; 330; birth order; parental investments; occupational outcomes; intergenerational mobility; marriage; fertility